2020
DOI: 10.2174/2215083805666190807111817
|View full text |Cite
|
Sign up to set email alerts
|

Natural Phytochemicals and Their Therapeutic Role in Management of Several Diseases: A Review

Abstract: Introduction: These days, a lot of people face some health-related problems in day to day life. The conventional synthetic medicine is not effective enough to cure them alone. The conventional therapy for the management of these health-related issues involves the use of hazardous synthetic chemicals and surgical diagnosis, which have lots of serious side effects. It is necessary to conduct research on herbal medicines, this is an alternative approach to avoid the side effects of synthetic medicines to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The World Health Organization reported that 80% of the world population depend on traditional medicine for their primary health care needs 25 . The majority of treatment methods in traditional medicine utilizes biologically active herbal extracts and their phytoconstituents which inherit a vast range of medicinal and pharmacological properties against numerous chronic as well as acute diseases and disorders 26 . In this study, three selected plant parts which are used in the RA medications of ayurvedic medicine were subjected to qualitative and quantitative analysis of phytochemicals followed by the evaluation of their in-vitro antioxidant and antiinflammatory activities.…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization reported that 80% of the world population depend on traditional medicine for their primary health care needs 25 . The majority of treatment methods in traditional medicine utilizes biologically active herbal extracts and their phytoconstituents which inherit a vast range of medicinal and pharmacological properties against numerous chronic as well as acute diseases and disorders 26 . In this study, three selected plant parts which are used in the RA medications of ayurvedic medicine were subjected to qualitative and quantitative analysis of phytochemicals followed by the evaluation of their in-vitro antioxidant and antiinflammatory activities.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking analysis will not only serve to unravel the BPA's toxicity mechanism and facilitate the identi cation and development of chemoprotective drugs against BPA-induced toxicity but also to support in vivo ndings related to BPA-induced toxicity, thereby enhancing con dence in this research outcome (Johnson et al, 2023). Medicinal plants remain the natural depot for many of these drugs that in turn confer the broad-spectrum pharmacological activity on the former (Shirsath & Goswami, 2020). One of the medicinal plants is Ficus exasperata Vahl leaf (FEVL), a Sandpaper leaf tree belonging to the Moraceae family of g plants (Ahmad et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on medicinal plants are now being conducted, and the development of medications using natural substances that are beneficial has opened up new opportunities for the association of doctors and chemists. 4 As a result, one-third of the currently used pharmaceuticals in the human population are manufactured from natural and herbal sources, and doctors think that patients should be encouraged to take herbal plants because of how well-tolerated and successful they are at stopping tumor growth. Therefore, naturally generated anticancer agents must be developed as an alternative safe, affordable, and practical method for cancer treatment as traditional cancer medicines have failed to satisfy the requirements for successful cancer therapy.…”
Section: Introductionmentioning
confidence: 99%